Impact of corruption on economic growth in the MENA region: An empirical analysis from 2000-2020 - Fayad, Nour M.; Taher, Hanadi (Edelweiss Applied Science and Technology, 2024)
This paper examines the impact of corruption on the economic growth of the Middle East and North African (MENA) countries through a modified Cobb-Douglas production function augmented for various corruption indices. The primary objective is to compare different corruption measures, such as the Corruption Perception Index, the Control of Corruption indicator from Worldwide Governance Indicators, and a newly developed Customized Corruption Index for their impacts on economic output. Using the ARDL econometric analysis, this paper gauges the effects of corruption on GDP growth in the MENA region, using data from the World Bank and Transparency International between 2000 and 2020. Results indicated that corruption does deter economic growth significantly, though at varying variables of corruption indices. These findings give reason to emphasize how important the accuracy of corruption measurement is in economic analysis, in contrast, decreased corruption may prove to be, in fact, the real driver of economic improvement in the MENA region. The paper contributes to the literature by underlining the economic costs of corruption and, based on evidence, makes some recommendations for policymakers seeking to foster economic development through better governance.